2010
DOI: 10.1007/s11145-010-9256-9
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic characteristics speed Hindi word naming but slow Urdu naming: evidence from Hindi/Urdu biliterates

Abstract: Two primed naming experiments tested the orthographic depth hypothesis in skilled biliterate readers of Hindi and Urdu. These languages are very similar on the spoken level but differ greatly in script; Hindi is a highly transparent script, whereas Urdu is more opaque. It was accordingly hypothesized that formbased priming would be greater for Hindi than Urdu, reflecting greater reliance on a phonological assembly route in the more transparent Hindi script. Proficient Hindi/ Urdu biliterate readers were presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 47 publications
(56 reference statements)
1
31
0
Order By: Relevance
“…The effects of Arabic letter complexity were also reported by Rao et al (2011). They compared the speed of written word recognition in readers of Urdu and Hindi.…”
Section: Diversity In Writing Systemsmentioning
confidence: 92%
See 1 more Smart Citation
“…The effects of Arabic letter complexity were also reported by Rao et al (2011). They compared the speed of written word recognition in readers of Urdu and Hindi.…”
Section: Diversity In Writing Systemsmentioning
confidence: 92%
“…However, Hindi is written in Devanāgarī orthography, which is an abugida, and Urdu is written using a variation of the Perso-Arabic orthography, which is an abjad. Rao et al (2011) found that even native Urdu speakers and readers, whose second language was Hindi, recognized words faster in Hindi than in Urdu. They interpreted this as reflecting the higher degree of visual complexity in the Arabic orthography than in the Hindi orthography.…”
Section: Diversity In Writing Systemsmentioning
confidence: 96%
“…Brown et al (1984) examined the size of repetition priming in Hindi-Urdu bi-scriptal readers. Hindi and Urdu are morphologically and phonologically identical at the spoken level but differ in their script: Hindi is written from left to right in a shallow script with discrete letters, while Urdu is written from right to left in an opaque script modeled on Persian and Arabic (see Rao et al 2011). Brown et al (1984 examined repetition priming for Hindi and Urdu words preceded by primes presented in the same or different script.…”
Section: Introductionmentioning
confidence: 99%
“…Deep orthographies have complex mappings (e.g., standard writing conventions for English, Mandarin Chinese and Hebrew), while shallow orthographies more closely approximate the ideal one-to-one mapping (Korean Hangul, Japanese Kana, Spanish alphabet). The Orthographic Depth Hypothesis holds that shallower orthographies will be easier to learn due to their more consistent mappings from grapheme to linguistic unit, and that in such writing systems phonology will play a more prominent role in lexical access than will be the case for deeper orthographies (Frost et al, 1987;Frost & Katz, 1989;Katz & Frost, 1992;Rao et al, 2011;Schmalz et al, 2015).…”
mentioning
confidence: 99%
“…For example, the Mandarin language is rendered in print using at least three different orthographies grounded in two different design principles: morpho-syllabic traditional characters in Taiwan, morpho-syllabic simplified characters in the Peoples Republic of China and alphabetic pinyin in the early grades in both (Cheung & Ng, 2003). In fact, it may not be unusual for the same language, or minimally different language varieties, to be written with very different scripts, as in the cases of Serbian/Croatian (Feldman et al, 1985; and Hindi/Urdu (Rao et al, 2011). Moreover, two orthographies may be superficially similar in that they make use of the same script, yet map to languages that differ subtly (AAE/MAE) or markedly (English/Dutch) from one another.…”
mentioning
confidence: 99%